Composition Of Fish Catch Using Gillnet Opereted In The Afternoon And Night In Paluh Sibaji Village, Pantai Labu District, Deli Serdang Regency, Sumatera Utara Province - Lubis, Sarma Uli; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted date on 03 march until 09 march 2014 in Paluh Sibaji village, Pantai Labu District, Deli Serdang regency, Sumatera Utara province. The aim of this research was undertand the difference in spesies and composition cath fish using gillnet in the afternoon and night.This research was using survey method. Using gillnet done juring 7 day. While water quality parameters measured in descriptif.The result shown that there were 5 species in the afternoon and night. Grith in the afternoon is 392 Kg and grith in the night is 320 Kg, olso grith total 712 Kg. The species that cathed fish and lobster.This research showed that there is no difference of the result cath in the afternoon and night. Resulth of Chi-square test shown that there was no difference composition of the result cath gillnet in the afternoon and night.Keyword : Gillnet, afternoon, night, Sumatera Utara